VAT Productivity in Nepal: A Study of C Efficiency in Nepal - Shrestha, Narasagar (Shahid Kirti Multidisciplinary Journal, 2025)
As of 2018 out of 193 un member countries of the UNO there are 176 countries in the world which have enacted the VAT legislations and Nepal was 107 th country in the list of countries which implemented it in 1997. (ITD, 2023) During this time the Nepalese economy has undergone significant changes in terms of size and structure. The VAT productivity is measured by using different types of ratios and C efficiency ratio is the major one. The value of c efficiency ratio of Nepal is greater than the ratios of sub-Saharan Africa and other African countries but lower than all other parts of the world. There is a weak positive correlation between increase in share of service sector in the GDP, increase in per capita income, urbanization, trade competitiveness and decrease in the share of agriculture in the GDP. Due to lockdown during COVID-19 Pandemic 2019, both Tax GDP ratio and VAT GDP ratio decreased. As a result of this the value of C efficiency also decreased. The number of non-filer tax payers, outstanding amount of VAT dues and zero return shows the ineffectiveness of the VAT administration. So, it is recommended to set up a separate department for VAT administration and an expert committee to study impact of macroeconomic variables in the performance4 of VAT in Nepal